Development of image-based method for the quantitative assessment of cartilage damage from CT as a biomarker in osteoarthritis - Zheng, J-Q (2024)
Preclinical studies, like those for drug development, require quantitative methods to assess osteoarthritis (OA). In OA, cartilage damage and subchondral bone deformations are critical indicators. Therefore, this thesis introduces and validates two innovative frameworks for automated OA assessment, centering on the image analysis of cartilages and subchondral bones.